A Compact Microstrip Spiral Antenna Embedded in Water Bolus for Hyperthermia Applications. (9th April 2013) - Korkmaz, Erdal; Isik, Omer; Nassor, Mohammed Ahmed
Abstract : This paper presents the design, simulation, fabrication, and measurement of a circular spiral microstrip antenna embedded in distilled water bolus. The antenna is mainly designed to operate at 434 MHz ISM band to be used for a hyperthermia applicator. The performance of the antenna is compared to a conventional patch antenna also embedded in water bolus. The results show that spiral antenna has significant narrower radiation pattern and is capable to operate at multiple frequencies as well. Narrow beam of the antenna is desired to design a multiantenna arrangement with less coupling and a better focusing resolution which can be crucial for deep regional hyperthermia applications. The option of other frequencies is desirable to have a better control over the penetration depth versus focusing depending on the application region.